Evaluating the Technical, Economic and Environmental Efficiencies of Biomass Co-firing Technology in Coal Thermal Power Plants in Vietnam: Online First: 17/06/2026 - Vo, Kien Quoc (Journal of Technical Education Science, 2026)
This paper presents the results of theoretical research on co-firing technology in coal power plants. In this paper, co-firing technologies were evaluated. The results show that, in Vietnam’s conditions, with operating power plants, direct co-firing technology is the most suitable. Besides, the effects of co-firing have also been analyzed based on the operating experience of plants that have applied co-firing technology in the world. In addition, the assessment of the economic and environmental benefits of co-firing technology have also been carried out based on theoretical calculations for the 600 MW unit of Song Hau power plant. The results show that with the price difference between coal and biomass being insignificant and the CO2 emissions trading market not yet approved, co-firing will not be economically beneficial. However, the additional cost per GWh of electricity is negligible and acceptable. The advantage of co-firing technology is that it always has environmental and social benefits that do not depend on fuel costs.